Peripheral semantics of the word as a marker of the national picture of the world / Tetiana O. Anokhina ... [et al.] - O. Anokhina, Tetiana; M. Mashkina, Olena; B. Melko, Khrystyna; I. Poznikhirenko, Yuliia; O. Teslenko, Natalia (Universiti Teknologi MARA, 2021)
Previous studies emphasized that there is a close connection between speech and thinking. The paper analyses the peripheral semantics of the German language's active vocabulary units to define how they represent the features of the national, linguistic picture of the world, namely, the mental traits of the German ethnos. Semantic methods and the extrapolation methods of typical secondary values on non-nonmetal characteristics are used mainly; the comparative method was partially used. The contextual method was used as an auxiliary method for illustrating common ethical, aesthetic, and pragmatic guidelines (presuppositions) and stereotypes. The paper carried out: a) semantic analysis of peripheral lexical-semantic variants of arbitrarily and expediently selected notional parts of speech; b) comparison of peripheral semantics of similar words of German and Russian languages against the background of the Russian language; c) clarification of ethnological connotation of individual German isms found in the Russian language. The article proves that peripheral semantics in its lexico-semantic, seismological, and lexicographical understanding expresses key symptom complexes of German mentality, which can be expressed by concepts order, accuracy, family, wealth, quality, practicism and etc. It is found that the German linguistic picture of the world in comparison with the Russian one the material is marked by the minimalism of estimated values, practical orientation and is alluded to bookish style.